'Very demanding. Extremely rewarding': Exploring the co‐occurrence of burnout and engagement in alcohol and other drug workers. (3rd February 2021) - Skinner, Natalie; Roche, Ann M.
Abstract: Introduction: Alcohol and other drug (AOD) work can be highly meaningful and satisfying, but also intense and highly demanding. This combination often creates significant strain for workers. Mirroring this complexity, this study considered the predictors and outcomes of the concurrent experience of burnout and engagement in AOD workers. The Job Demands‐Resources model informed the study. Methods: This study utilised data from a recent Australian AOD workforce survey. The sample comprised 886 workers in direct client service roles. K‐means cluster analysis on burnout and engagement measures identified four discrete groups: burnt out (15.6%) (high burnout/low engagement), engaged (36.7%) (low burnout/high engagement), overextended (26.5%) (high burnout/high engagement) and indifferent (21.2%) (low burnout/low engagement). Results: Multinomial logistic regression analysis indicated that workers were more likely to be burnt out or overextended, rather than engaged, if they reported high work intensity, low organisational openness to change and low support. Multivariate analysis of variance showed burnt‐out workers had the least favourable and engaged respondents the most favourable outcomes on job satisfaction, turnover intention, health and life quality. Overextended workers were comparable to indifferent workers on these outcomes. Discussion and Conclusion: This study offers a unique and nuanced view of AOD worker wellbeing. For the one‐quarter of workers reporting simultaneous burnout and engagement, their enthusiasm and commitment did not protect them from poor personal and organisational outcomes typically linked with burnout. The need for systemic and structural interventions is clearly indicated, including open and supportive organisational cultures, leadership development and adequate staffing.